2017
DOI: 10.1055/s-0037-1605361
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Diabetes Abolishes the Antithrombotic Effect of Clopidogrel in Apolipoprotein E–Deficient Mice

Abstract: Patients with acute coronary syndrome with diabetes mellitus (DM) exhibit an impaired platelet inhibitory response to clopidogrel which is only partially understood. DM was induced by the administration of streptozotocin (STZ) to 9-week-old mice. The antithrombotic effects of clopidogrel (10 mg/kg/d, orally × 5 days) were determined using a FeCl3-induced thrombosis model employing wild-type (WT), apolipoprotein E (apoE)-deficient, and diabetic apoE-deficient mice at 21 weeks. Antiplatelet effects were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The animals (mice) were divided into 4 groups of 10 animals. The animals were administered GRS compound in 10 mg/kg dose or clopidogrel (Plavix®, 75 mg film-coated tablets, Sanofi Winthrop Industry, France, lot АА686, expiration date -01.04.2023) in median effective dose 10 mg/kg once orally for 3 days [4]. Control group rats received 0.5 % aqueous carboxymethyl cellulose solution.…”
Section: Thromboembolism Modelmentioning
confidence: 99%
“…The animals (mice) were divided into 4 groups of 10 animals. The animals were administered GRS compound in 10 mg/kg dose or clopidogrel (Plavix®, 75 mg film-coated tablets, Sanofi Winthrop Industry, France, lot АА686, expiration date -01.04.2023) in median effective dose 10 mg/kg once orally for 3 days [4]. Control group rats received 0.5 % aqueous carboxymethyl cellulose solution.…”
Section: Thromboembolism Modelmentioning
confidence: 99%
“…Finally, platelet inhibitory activity of clopidogrel was also shown to be reduced in DIO mice compared to controls [ 141 ]. In another preclinical study using wild-type apolipoprotein E (apoE) mice and diabetic apoE deficient mice, it was shown that platelet inhibition by clopidogrel was reduced in diabetic mice compared to wild-types [ 142 ].…”
Section: Clopidogrel: a Specific Example Of Phenoconversion In T2dmmentioning
confidence: 99%